Some notes on the study of fractals in fracture - Lu, Chunsheng (Engineers Australia, 2007)
In this paper, some exciting advances in the application of fractals in fracture over the last two decades are briefly reviewed and a few controversial issues are discussed. The main topics include fractality of fracture surfaces, relationships between fractal dimension and toughness, scaling and universality in fracture, fractal fracture mechanisms, and their implications for fabrication of novel materials. Also highlighted are several open problems and continuing challenges in this multidisciplinary field.